7x-(4x-1)=2

Simple and best practice solution for 7x-(4x-1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-(4x-1)=2 equation:


Simplifying
7x + -1(4x + -1) = 2

Reorder the terms:
7x + -1(-1 + 4x) = 2
7x + (-1 * -1 + 4x * -1) = 2
7x + (1 + -4x) = 2

Reorder the terms:
1 + 7x + -4x = 2

Combine like terms: 7x + -4x = 3x
1 + 3x = 2

Solving
1 + 3x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 3x = 2 + -1

Combine like terms: 1 + -1 = 0
0 + 3x = 2 + -1
3x = 2 + -1

Combine like terms: 2 + -1 = 1
3x = 1

Divide each side by '3'.
x = 0.3333333333

Simplifying
x = 0.3333333333

 

You can always share this solution

See similar equations:

| 4(x+6)=x+(x-7) | | (12+2x)(18+2x)= | | 12x-3x+4=7+2x+9 | | 2x+-7=90 | | 4(q-12)=2-6q | | 6y+-15=360 | | b^2=24-5b | | 2x+-7=360 | | 6y+-15=180 | | (20+2x)(30+2x)= | | 125-3x=6x+8 | | -22-2x=9-10x | | (y-1)+(2y-3)+(3y-9)=180 | | 221-5x=31x+17 | | 9-8x=66-29x | | (20+2x)(26+2x)= | | 3x+12=54-3x | | 4+7x=64+x | | 36s^2-25=0 | | 4x+33=12x-31 | | 28x^3-21x^2+7x=0 | | (12x-9)=(13x-19) | | 10x+5=8x+13 | | (10+2x)(18+2x)= | | (2x-1)+(x+4)=0 | | 2x-4=3x+7 | | 9x+10=x-26 | | 4x^2+92x+520=832 | | 13x+2=20x-5 | | 4y-17=-2(5-y) | | 5x+3=-9x-39 | | -4x+2=10x-20 | | 4x^2+92x+520= | | 9x+3=6x+8 | | 4(3x-1)=11x-3(x-4) | | 4x-5y+3x+11y= | | 4x-5y+3x= | | -3x+6+8x= | | (8x-12)= | | 0.25x^2=25 | | 20(3x-x)= | | -2(4x-6)= | | -6r-5=7-12r | | 12t+(1-7t)=31 | | 3(4x-5)= | | 7x+13y=78 | | 25d^2-100=0 | | 36n^2=1 | | 8x^4-48x^3-56x^2=0 | | 2x^3-4x^2+2x=0 | | 4a-(3-a)=17 | | x^3+2x^2-3x=0 | | x^3+12x^2+36x=0 | | 16y^2-2y-3=0 | | 3x-28+x=22 | | -7-18x+9x^2=0 | | 5x-8y=16 | | 2p^2=-21p-41 | | X^3+5x+6=0 | | 2k^2-40=-11k | | 5x^3+10x^2+5x=0 | | 4(6z-1)-5(z+4)=11(z+1) | | -2(a+b)= | | 8b-(3b+4)=11 | | 12x^2-5x=0 |

Equations solver categories